1998
DOI: 10.1111/j.1600-079x.1998.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of plasma melatonin concentrations by changes in posture

Abstract: Posture change from a lying position to a standing position results in a decrease in plasma volume, which leads to an increase in plasma constituents, especially that of proteins and blood constituents bound to them. The aim of the present study was to investigate the physiological effects of postural changes on plasma nocturnal melatonin concentrations in healthy human volunteers. The study was divided into four stages. During stage one, subjects were seated from 21.00 hr to 01.00 hr. In stage two, subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
(12 reference statements)
1
15
1
Order By: Relevance
“…Such effects have been reported in animal studies in which light exposure and physical activity were carefully controlled [41–43], and in blind individuals [44] and more recently also in sighted subjects [45]. Our data confirm previous findings that posture affects plasma melatonin concentrations with lower melatonin levels during supine positions [46, 47]. A standing position results in a redistribution of the blood onto the lower parts of the body, which includes the dependent arms and legs.…”
Section: Discussionsupporting
confidence: 90%
“…Such effects have been reported in animal studies in which light exposure and physical activity were carefully controlled [41–43], and in blind individuals [44] and more recently also in sighted subjects [45]. Our data confirm previous findings that posture affects plasma melatonin concentrations with lower melatonin levels during supine positions [46, 47]. A standing position results in a redistribution of the blood onto the lower parts of the body, which includes the dependent arms and legs.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that posture can influence melatonin concentration in some studies (37,38) but not in other studies (39). Although the effect of posture on melatonin concentration remains controversial (40), illuminance at eye level varies depending on posture.…”
Section: Discussionmentioning
confidence: 98%
“…During each admission, no restrictions were placed on posture (although subjects were recumbent most of the time). We think that the effects of posture on melatonin levels remain unclear: 2 groups have reported a modest increase in melatonin levels when subjects change their posture from supine to standing (Deacon and Arendt, 1994;Nathan et al, 1998), another reported a modest decrease in the subjective day during a forced desynchrony protocol under dim light conditions (Shanahan and Czeisler, 2000), and a fourth group reported no effect (Voultsios et al, 1997). Subjects were not allowed to engage in physical exercise, but otherwise no restrictions were made on physical activity.…”
Section: Methodsmentioning
confidence: 97%